2013
DOI: 10.1136/thoraxjnl-2013-203538
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of parental and active smoking on early lung function deficits: a prospective study from birth to age 26 years

Abstract: Background Cross-sectional reports have suggested that, among active smokers, previous exposure to parental smoking may increase susceptibility to development of chronic obstructive pulmonary disease. We assessed prospectively whether parental smoking enhances the effects of active smoking on early deficits of lung function in young adults. Methods We used data from the prospective birth cohort, the Tucson Children’s Respiratory Study. Maternal and paternal smoking was assessed via questionnaires completed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 25 publications
(25 reference statements)
10
58
1
1
Order By: Relevance
“…Follow-up of participants from the Tucson Children’s Respiratory birth cohort study through first 26 years of life has demonstrated that ETS exposure in utero and during early life increases the susceptibility to the harmful effects of active smoking in early adulthood and an accelerated decline in lung function [67]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up of participants from the Tucson Children’s Respiratory birth cohort study through first 26 years of life has demonstrated that ETS exposure in utero and during early life increases the susceptibility to the harmful effects of active smoking in early adulthood and an accelerated decline in lung function [67]. …”
Section: Resultsmentioning
confidence: 99%
“…Maternal smoking reduces infant lung function which is associated with impaired lung volume in adulthood (both for FEV1 and forced vital capacity (FVC)), independent of smoking in adulthood, compounding the effect of smoking to reduce airflow limitation and increasing the risk of COPD [92]. Parental smoking was also responsible for a rapid decline in FEV1:FVC ratio in young adulthood even more (3%) than that of smokers not exposed to parental smoke [67]. The majority of studies focused on airflow limitation (FEV1 and FEV1:FVC) as a marker of ETS-exposure-related airway obstruction [92].…”
Section: Resultsmentioning
confidence: 99%
“…Aside from anatomical origins, several studies argue for the additive role of dynamic processes in the airways of preterm-born subjects, with on-going disease, that may be induced by preterm birth per se and postnatal environmental factors 11. Lifelong environmental factors may have a deleterious synergistic effect, like environmental tobacco smoke exposure in infancy and later active smoking 12. Here, we provide arguments for an independent impact of a postnatal clinical factor, preschool wheeze, on alterations of lung function in preterm-born subjects at adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…The previously mentioned meta-analysis of 79 prospective studies found an 18-70% higher incidence of wheezing in children exposed to postnatal maternal smoking (OR 1.70 in children f2 years of age) [42]. Prospective birth cohort studies following children up to adult age showed a persistence of the harmful effects of prenatal and postnatal tobacco smoke exposure [46][47][48][49]. In a birth cohort of 1314 children from Germany, maternal smoking during pregnancy almost doubled the risk of asthma at the age of 20 years [49].…”
Section: Second-hand Smoke Exposurementioning
confidence: 99%